EFFECT OF INTERNODES NUMBER AND CONCENTRATION OF ROOTONE-F PLANT GROWTH REGULATOR ON GROWTH OF PEPPER (Piper nigrum L.) CUTTINGS - Van Basten; Lagiman Lagiman; Suwardi Suwardi (Jurnal Agrivet, 2019)
Pepper (Piper nigrum L.) is one of the spice plants that have high export value and propagated by cuttings. Use of internodes number and growth regulator were needed as a way to provide a good of planting material through cuttings. This research aimed to determine the best interaction between internodes number and concentration of Rootone-F growth regulator on growth of pepper (Piper nigrum L.) by cuttings. This research was carried out in experimental garden of Agriculture Universitas Pembangunan Nasional “Veteran” Yogyakarta, Ngemplak, Sleman, Yogyakarta, since February – May 2019. This research used a Randomized Block Design (RBD) with two factors. The first factor was internodes number which were one, two and three internodes. The second factor was concentration of Rootone-F which were 50 ppm, 100 ppm, and 150 ppm. So there were 3 x 3 = 9 treatments combination. Cuttings wit seven intenodes without Rootone-F were used as control. The result showed there were no interaction from two treatments in each parameter. There were no significant difference between control and treatment of each parameter. Internodes number has significantly affected in paramater percentage of life, day of emergence shoot, shoot length, number of leaves, number of root, root volume and shoot dry weight with the best result were cutting with 3 internodes. Concentration of Rootone-F has significantly affected in parameter percentage of life and day of emergence shoot, concentration 100 ppm and 150 ppm better than 50 ppm.Keyword: Pepper plant, cuttings, internodes, Rootone-F.